EXCEPTIONAL AND STRIKING 3D TRACK-DETACHED UNDERTRACK SPECIMENS FROM THE UPPER JURASSIC OF ASTURIAS (N SPAIN) - LAURA PIÑUELA; JOSÉ CARLOS GARCÍA-RAMOS; KAREN MORENO; GIUSEPPE LEONARDI; OSCAR EUGENIO FINSTERBUSCH-LAGOS (Rivista Italiana di Paleontologia e Stratigrafia)
Vertebrate palaeoichnology often aims at the identification of the trackmaker by associating diagnostic features from the known taxa’s skeletal anatomy with its inferred footprint morphology, but deep penetrative tracks and/or deep, detached undertracks (DDU) are providing conflicting morphological/extra-morphological information, bringing into question the initially assumed close anatomical correlation.